Impact of e-cigarette vaping aerosol exposure in pregnancy on mTOR signaling in rat fetal hippocampus - Lee, Jehoon; Orzabal, Marcus R.; Naik, Vishal D.; Ramadoss, Jayanth (Frontiers in Neuroscience, 2023)
Electronic cigarette (e-cig) use during pregnancy has become a major health concern in recent years and many view them as less harmful and may help quit or reduce combustible cigarettes. Implementing a state-of-the-art engineered vaping system, comprising an atomizer similar to those sold in vape shops, we aimed to utilize a translational e-cig inhalation delivery method to provide crucial information on the impact of prenatal e-cig aerosols on the developing brain hippocampal mTOR system in a rat model system. Gestational e-cig vaping significantly increased P-mTOR levels (p < 0.05) in the rat fetal hippocampi in the nicotine group (comprising of VG/PG + nicotine) compared to the control and the juice (comprising of VG/PG) groups. Total mTOR expression was not different among groups. Immunofluorescence imaging demonstrated P-mTOR was detected exclusively in the granule cells of the dentate gyrus of the fetal hippocampus. E-cig did not alter DEPTOR, but RAPTOR and RICTOR were higher (p < 0.05) in the Nicotine group. Gestational e-cig vaping with nicotine increased (p < 0.05) the activity and expression of 4EBP1, p70S6K, but decreased (p < 0.05) P-PKCα in the fetal hippocampi. In summary, dysregulation of mTORC1 and the related mTORC2, their activity, and downstream proteins together may play a critical role in e-cig-vaping-induced neurobiological phenotypes during development.